Implementasi Pendidikan Karakter dalam Mengatasi Krisis Moral di Sekolah - Saiful Bahri (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2015)
Character education is the deliberate effort (conscious) to help people understand, care about, and implement the core ethical values. It is expected that character and personality are formed by the learners themselves who long for the success of character education. Learners are expected to understand the values imparted to him, entirely without any misunderstanding at all. Integration of character education is vital in overcoming the problem of moral crisis. Thus, in the implementation of character education in schools is three methods are employed involving learning, extracurricular activities, and school culture.